ABIN1 alleviates inflammatory responses and colitis via facilitating A20 activity. (July 2020) - Pu, Tian; Liu, Wenzheng; Wu, Yijun; Zhao, Ye
Background: Macrophages-mediated inflammation is involved in the progress of colitis. The present study aims to explore the roles of A20-binding inhibitor of NF-κB (ABIN1) in the macrophages and its underlying mechanisms. Methods: ABIN1 myeloid cell-conditional transgenic mice were established and genotyped by PCR and immunoblotting assays. Tumor necrosis factor (TNF)-α was applied to pre-treat bone marrow-derived macrophages (BMDMs) in the presence of lipopolysaccharide. The mRNA and protein levels of pro-inflammatory cytokines were determined by qRT-PCR and ELISA, respectively. Dextran sulfate sodium (DSS)-induced colitis was established to determine the effects of ABIN1 on the survival time, body weight, colon length, and colon histopathological changes. Western blotting was applied to determine the expressions of signaling proteins. Results: ABIN1 overexpression did not affect cell populations of macrophages and neutrophils in mice. Its overexpression reduced the productions of pro-inflammatory cytokines in BMDMs and ameliorated survival rate and colitis symptoms in the DSS-induced mouse model. The underlying mechanisms revealed that ABIN1 impaired macrophages-mediated inflammatory responses, in part by regulating the NF-κB signal pathway, and its ameliorated effects on the symptoms of DSS-induced colitis were associated with A20/tumor necrosis factor α-induced protein 3 (TNFAIP3). Conclusion: ABIN1 attenuated inflammatory responses and colitis by regulating A20/TNFAIP3 activities.